Novel Homozygous Missense Mutation in the ARG1 Gene in a Large Sudanese Family - Elsayed, Liena E. O.; Mohammed, Inaam N.; Hamed, Ahlam A. A.; Elseed, Maha A.; Salih, Mustafa A. M.; Yahia, Ashraf; Abubaker, Rayan; Koko, Mahmoud; Abd Allah, Amal S. I.; Elbashir, Mustafa I.; Ibrahim, Muntaser E.; Brice, Alexis; et al. (Frontiers in Neurology, 2020)
Background: Arginases catalyze the last step in the urea cycle. Hyperargininemia, a rare autosomal recessive disorder of the urea cycle, presents after the first year of age with regression of milestones and evolves gradually into progressive spastic quadriplegia and cognitive dysfunction. Genetic studies reported various mutations in the ARG1 gene that resulted in hyperargininemia due to a complete or partial loss of arginase activity. Case presentation: Five patients from an extended highly consanguineous Sudanese family presented with regression of the acquired milestones, spastic quadriplegia, and mental retardation. The disease onset ranged from one to three years of age. Two patients had epileptic seizures and one patient had stereotypic clapping. Genetic testing using whole-exome sequencing, done for the patients and a healthy parent, confirmed the presence of a homozygous novel missense variant in the ARG1 gene [GRCh37 (NM_001244438.1): exon 4: g. 131902487T>A, c.458T>A, p.(Val153Glu)]. The variant was predicted pathogenic by five algorithms and affected a highly conserved amino acid located in the protein domain Ureohydrolase, Arginase subgroup. Sanger sequencing of 13 sampled family members revealed complete co-segregation between the variant and the disease distribution in the family in line with an autosomal recessive mode of inheritance. Biochemical analysis confirmed hyperargininemia in five patients. Conclusion: This study reports the first Sudanese family with ARG1 mutation. The reported variant is a loss of function missense mutation. Its pathogenicity is strongly supported by the clinical phenotype, the computational functional impact prediction, the complete co-segregation with the disease, and the biochemical assessment. Keywords: Hyperargininemia, ARG1 gene, Whole-exome sequencing, Sudan.